2019
DOI: 10.1111/cas.14008
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor activity of Raddeanin A is mediated by Jun amino‐terminal kinase activation and signal transducer and activator of transcription 3 inhibition in human osteosarcoma

Abstract: Osteosarcoma is the most common primary malignant bone tumor. Raddeanin A ( RA ) is an active oleanane‐type triterpenoid saponin extracted from the traditional Chinese herb Anemone raddeana Regel that exerts antitumor activity against several cancer types. However, the effect of RA on osteosarcoma remains unclear. In the present study, we showed that RA inhibited proliferation and induced apoptosis of osteosarcoma cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…Osteosarcoma is the commonest non-hematological malignancy of bone in children aged 15–19 years with highly aggressive and systemic metastasis, and characteristically occurs around the growth plate of long bones [17]. In recent decades, a large number of lncRNAs ranging in size from several hundred base pairs to tens of thousands base pairs have been clarified as a novel group of cancer-related non-coding RNAs (ncRNAs) in human.…”
Section: Discussionmentioning
confidence: 99%
“…Osteosarcoma is the commonest non-hematological malignancy of bone in children aged 15–19 years with highly aggressive and systemic metastasis, and characteristically occurs around the growth plate of long bones [17]. In recent decades, a large number of lncRNAs ranging in size from several hundred base pairs to tens of thousands base pairs have been clarified as a novel group of cancer-related non-coding RNAs (ncRNAs) in human.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 is transcription factor that involved in growth and metastasis in several types of cancer cell (22,23). STAT3 is highly expressed in osteosarcoma and may be a key molecular target for developing drugs for human osteosarcoma (24).…”
Section: Discussionmentioning
confidence: 99%
“…An in vivo study following exposure of RA in ROS xenograft models also confirmed the anti-cancer effects of RA on human osteosarcoma. Zhuoying and coworkers [124] suggested that RA treatment induced apoptosis and abrogated proliferation in osteosarcoma cells through modulation of the JNK/c-Jun and STAT3 signaling pathways. An in vivo study on tibial xenograft tumor model, administration of apoptosis in OS cells, which lead to the reduction of tumor size.…”
Section: Osteosarcomamentioning
confidence: 99%